Simulating MADMAX in 3D: requirements for dielectric axion haloscopes. Issue 10 (12th October 2021) - Knirck, S.; Schütte-Engel, J.; Beurthey, S.; Breitmoser, D.; Caldwell, A.; Diaconu, C.; Diehl, J.; Egge, J.; Esposito, M.; Gardikiotis, A.; Garutti, E.; Heyminck, S.; et al.
Abstract: We present 3D calculations for dielectric haloscopes such as the currently envisioned MADMAX experiment. For ideal systems with perfectly flat, parallel and isotropic dielectric disks of finite diameter, we find that a geometrical form factor reduces the emitted power by up to 30 % compared to earlier 1D calculations. We derive the emitted beam shape, which is important for antenna design. We show that realistic dark matter axion velocities of 10 -3 c and inhomogeneities of the external magnetic field at the scale of 10 % have negligible impact on the sensitivity of MADMAX. We investigate design requirements for which the emitted power changes by less than 20 % for a benchmark boost factor with a bandwidth of 50 MHz at 22 GHz, corresponding to an axion mass of 90 μ eV. We find that the maximum allowed disk tilt is 100 μ m divided by the disk diameter, the required disk planarity is 20 μ m (min-to-max) or better, and the maximum allowed surface roughness is 100 μ m (min-to-max). We show how using tiled dielectric disks glued together from multiple smaller patches can affect the beam shape and antenna coupling.